1962
DOI: 10.1037/h0042110
|View full text |Cite
|
Sign up to set email alerts
|

The restricting effects of awareness: A paradox and explanation.

Abstract: Ss were shown tachistoscopically-presented word stimuli to test the distinction between the perceptual processes of registration (what could be called physiological or sensory threshold) and awareness (or the cognitive threshold). The presentation consisted of a stimulus word followed by series of words associated to the stimulus word either in terms of meaning or structural resemblance. Recall of words presented subliminally or supraliminally was facilitated with degree of awareness of actual stimulus word; w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
2
1

Year Published

1964
1964
1984
1984

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 15 publications
4
48
2
1
Order By: Relevance
“…analysis of variance (Table 2) shows that the difference between conditions is not significant, which indicates that our findings fail to replicate those of Spence and Holland (1962) on two counts. The subliminal stimulus did not enhance recall of CHEESE associates relative to a control condition, and supraliminal exposure of the stimulus did not restrict recall of associates relative to the subliminal condition.…”
Section: Food Deprivationcontrasting
confidence: 81%
See 1 more Smart Citation
“…analysis of variance (Table 2) shows that the difference between conditions is not significant, which indicates that our findings fail to replicate those of Spence and Holland (1962) on two counts. The subliminal stimulus did not enhance recall of CHEESE associates relative to a control condition, and supraliminal exposure of the stimulus did not restrict recall of associates relative to the subliminal condition.…”
Section: Food Deprivationcontrasting
confidence: 81%
“…The differences between subliminal and supraliminal groups were not significant (see last pair of t tests, Table 3), which indicates that heightened awareness of the stimulus did not restrict the degree of effect (as contrasted to Spence, 1964;Spence & Holland, 1962), nor enhance it, as is frequently assumed. The present data suggest that if the subject is sufficiently deprived, a very brief exposure of the stimulus is as likely to activate its associates as a prolonged exposure.…”
Section: Food Deprivationmentioning
confidence: 61%
“…The inference is based on an understanding of the creative and hypnotic experience as described in the present paper's introduction as well as some of the literature on subliminal perception (Shevrin, 1973;Spence & Holland, 1962) and alpha EEG (Martindale & Hines, 1975;Kamiya, 1969). The inference is bolstered by the positive results of the current investigation, but the crudeness of the inference must be acknowledged.…”
Section: Comparisons With Previous Datamentioning
confidence: 99%
“…Spence and Holland (1962) reported that conscious awareness of the stimulus has restricting effects on associations to the stimulus compared to associations to the same stimulus presented below the awareness threshold. In a study by Shevrin and Fritzler (1968), the incidence of alpha waves in EEG records was monitored during subliminal stimulation and during a subsequent "free association" period.…”
mentioning
confidence: 98%
“…Quizá los efectos distorsionantes de la expectativa y reestructuración que caracterizan a la percepción consciente no operan inconscientemente. Existen abundantes supuestos teóricos y algunos datos empíricos (Zuckerman, 1960;Spence y Holland, 1962;Posner, 1973;Shevrin y Dickman, 1980) que sugieren que los procesos cognitivos inconscientes pueden seguir principios de organización diferentes a los que rigen el procesamiento normal consciente.…”
Section: Percepción Subliminalunclassified